A educação de jovens e adultos no CEFET-MG: o olhar dos alunos (2006-2010) - Azevedo, Eliane Marchetti Silva (2010)
It is known that the school drop-out is a major problem which makes it especially difficult for Youth and Adult Education (EJA) in Brazil to achieve its intended objectives. In offering this modality of education, one of the greatest challenges faced by CEFET-MG has been to ensure the students persistence in these courses. Many of them drop out, postponing or even inhibiting the achievement of a diploma. Therefore, this research aims to investigate and analyze, from the point of view of the students who attend the integrated technical course in Constructions, offered in the PROEJA modality, which factors make them insist on their studies, how they realize the educational formation they have and the extent to which they exercise their citizenship in this context. Two semi-structured questionnaires were used for the purpose of classifying and pointing a demonstrative authority to the qualitative analysis. Furthermore, eight students and a servant of the school were heard with the objective of investigating issues related to the persistence of the students in the course and their exercise of citizenship. Once all the data was collected, it was possible to verify that the actions taken by the Fostering Education Program at CEFET-MG corroborate effectively to the persistence of these students. It was also possible to verify that the process of identification of these students as a team, the appropriation they make of their course and the consequent demand for their rights happen naturally. The students question the conditions under which the course is offered - from its institutional infrastructure to the pedagogical practice of the teachers, without assuming their own limitations and needs. We concluded that, as they struggle to assure their rights, guarantee their school seats, and conquest the desired professional skills, the students reflect upon their own situation, what leads them to increase their self-knowledge level and understand themselves as subjects of rights. This circumstance leads them into the movement of citizenship construction, which happens along their academic career. The EJA, by attending individuals marked by social exclusion, contributes to their rescue of the exercise of citizenship